Ecologías y promesas del giro microbiano - Charlotte Brives; Alexis Zimmer (Revue d'anthropologie des connaissances)
This issue of the Revue d'Anthropologie des Connaissances questions and puts into perspective the notion of a "microbial turn," which has appeared recently in the microbial social sciences field and more broadly in multispecies studies. After reiterating their definition and the definition of some associated notions, this introduction discusses them by contextualizing them within certain neglected traditions of the natural sciences and of a broader literature in the social sciences. This allows the authors to reengage on the one hand with a variety of narratives and approaches regarding human/microbe relationships that preceded this so-called turn, and on the other hand to highlight focal points of attention in regard to the promises attached to them. This effort to relativize the novelty and the promises of this "turn" is not intended to disqualify this notion, but to relocate it within infrastructures of wider practices and knowledge, in order to propose that it be taken up whilst giving careful attention to the conditions and political consequences of this turn.